Islamic Law and Contemporary Challenges from Fresh Ijtihad Point of View - Yusdani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The following article highlights how fiqh as a science is developed in the context of the dynamics and demands of humanitarian issues in the contemporary era. The main issue raised in this paper is how the reformulation of fiqh as a science can provide solutions and contribute to solving humanitarian problems such as human rights, the environment, the democratic system, local wisdom and others? To answer these various humanitarian problems, this paper starts from the framework of thought that fiqh as a science in addition to exploring its religious knowledge also needs to be integrated with the humanitarian sciences related to humanitarian issues that are developing at this time. In this way, it is expected that a fiqh study like this will be responsive and a solution to contemporary humanitarian issues. The approach used in this paper is a philosophy of science, history and deconstruction and reconstruction approach to the work of fiqh as science. Based on the results of studies that conducted, it can be concluded that for the development of fiqh as a science, a theoretical device is needed that requires the support of the human sciences that are developing in the contemporary era. That way, the model of fiqh studies with related human sciences is integrative that is multidisciplinary, interdisciplinary or even transdisciplinary.